Association between pre-chemotherapy serum levels of vitamin D and clinicopathologic findings in gastric cancer - Akbar Hedayatizadeh-Omran; Ghasem Janbabaei; Reza Alizadeh-Navaei; Omolbanin Amjadi; Jeyran Mahdavi Izadi; Versa Omrani-Nava (Babol University of Medical Sciences, 2020)
Background: To examine the serum levels of vitamin D in newly diagnosed gastric cancer (GC) patients compared with normal subjects and any possible association with prognostic variables. Methods: One-hundred subjects (50 GC and 50 controls) were enrolled and serum vitamin D levels were assessed using ELISA. Based on two definitions, vitamin D was classified as a sufficient level (≥30 ng/dL) and optimal level (25-80 ng/dL). The χ2 and unpaired t-test was used for data analysis with a significance level of 0.05. Results: The mean serum levels of vitamin D in patients and controls were 26.86 (±14.6) and 31.72 (±13.4), respectively (P=0.09). The prevalence of vitamin D insufficiency and deficiency was higher in GC cases than controls (P=0.045 if sufficient level ≥30 and P=0.065 if sufficient level ≥25). According to histological grade analysis, grade 3 patients (poorly differentiated) were found with significantly lower vitamin D concentrations in serum than grade 1 and 2 subjects (22.25 vs 33.29 ng/dL, P=0.021). No significant differences were observed between the two groups in pathological tumor-node-metastasis (pTNM) stages, distant metastasis, and location of the tumor. Conclusion: Higher prevalence of vitamin D insufficiency and deficiency in GC patients may reflect its role in malignancy; however, further studies are needed to confirm this relationship and any possible benefits to the patients.a